Optimizing Coffee Flavor Through Roasting and Manual Brewing Using Chemical and Sensory Approach: English - Elya Sukmawati; Setyo Pertiwi; Rokhani Hasbullah (PERTETA, 2025)
The global popularity of coffee has led to growing attention on how processing and brewing techniques influence its sensory attributes. This study analyzed the chemical content of coffee and assessed the combination of roasting and manual brewing methods on coffee flavor. The coffee types used were Arabica coffee and Robusta coffee. The roasts used were light, medium, and dark roast with AeroPress, Siphon, and V60 manual brewing methods. The experiment was arranged in a factorial arrangement within a Randomized Complete Block Design (RCBD), where coffee varieties served as blocks, and the treatment combinations of roasting and brewing methods were randomly assigned within each block. Data analysis includes two-way analysis of variance, biplot analysis, and the compromise programming method. The results showed that the selection of roast level and brewing method had a significant influence on the coffee's chemical analysis and sensory profile. Light roasting and complex flavors were more acceptable than dark roasting, which tends to be heavy. Based on the panelists' preference analysis using the compromise programming method, RLS (Robusta-Light roast-Siphon) emerged as the optimal choice, indicating that this combination balances all coffee taste criteria. The combinations ALV (Arabica-Light roast-V60), ALA (Arabica-Light roast-Aeropress), and AMA (Arabica-Medium roast-Aeropress) which tends to similar and provide a balanced, complex flavor profile, including aroma, acidity, and high overall quality. Arabica coffee combination ADS (Arabica-Dark roast-Siphon), ADA (Arabica-Dark roast-Aeropress), and ADV (Arabica-Dark roast-V60) which have less optimal visual and balance because dark roasting reduces the sensory criteria of coffee.